Novel biosensor for InterLeukin-6 detection - Huang, J.; Harvey, J.; Fam, W. H. D.; Nimmo, M. A.; Tok, I. Y. A. (Procedia Engineering, 2013)
Interleukin-6 (IL-6) is a pleiotropic cytokine with an important role in both immune regulation and exercise metabolism. During exercise, IL-6 is predominantly produced within, and released from, the working skeletal muscle, with the magnitude of IL-6 release related to the duration and intensity of the exercise bout. IL-6 (a) is the first cytokine to appear in circulation following initiation of exercise and (b) undergoes the most pronounced increase as compared to any cytokine in response to exercise. In the last decade, studies have suggested a role for IL-6 as a muscle energy sensor, pointing to its potential role as a biomarker of overtraining. Currently, ELISA and western blot is the staple detection technique for IL-6. However, they require substantial time, cost, machinery and specialist training. On the other hand, a Graphene Oxide-based amperometric sensor can provide real-time, low-cost yet sensitive protein detection. But, the coverage of mono-layered Graphene Oxide (GO) flake on SiO2 substrate is limited due to rinsing and unwanted crosslinking of the 3-AminoPropylTriEthoxy Silane (APTES) adhesion layer, thus leading to low available GO surface area, high variability of electrical conductivity between chips and low sheet transconductance that limits sensitivity of the sensor. This work had overcome this limitation by depositing carbon on the edges of GO flakes using an ethanol chemical vapor deposition (CVD). Then, the post-treated GO is fabricated into a liquid-gated biosensor and the detection window for IL-6 is presented. Our work yielded a highly conductive and electrically homogeneous carbon-based transducer to enable low-cost, facile, real-time yet sensitive amperometric sensors for IL-6.